Design, Build, and Implement Monitoring Applications Student Grades and Violations - Puteri Nurul Ma'rifah; Achmad Zain Nur; Luthfi Awwalia; Wildan Surya Wijaya; Puteri Nurul Magfirah (BEST, 2025)
Information and communication technology development has entered the era of Industry 4.0, requiring the educational sector to adapt more rapidly and efficiently. Thus, information technology has been integrated into various learning activities. However, the monitoring of information on students' learning progress is mostly carried out by the schools, while parents typically receive report cards at the end of the term. This does not provide effectiveness, as it limits parental involvement in early supervision. This research is designed to help both teachers and parents in supervising students more directly. This research utilizes NFC (Near Field Communication) technology for recording student attendance at school. Based on the results of application testing, users gave high ratings to the system in terms of interface design, NFC card reading accuracy, ease of managing student permissions, recording student behavior and academic grades, as well as the tool’s completeness and functionality. The average success rate of horizontal NFC card reading reached 100%, while vertical reading achieved 90%. The maximum reading distance was 4 cm for Samsung A50s (version 10.0) and Samsung A30s (version 10.0), and 3 cm for the Redmi Note 8 Pro (version 9.0).